Emotional scaffolding in text chats between Japanese language learners and native Japanese speakers. (1st September 2020) - Yoshida, Reiko
Abstract: The present study examines the kinds of emotional scaffolding that occurred in online text chats in Japanese between 19 learners of Japanese at an Australian university and 19 native‐speaking students at a Japanese university, together with the emotions that the learners experienced in relation to the scaffolding. The learners chatted in Japanese and also in English, each for 30 min per week for 7 weeks. The data that were collected consisted of questionnaires, chat transcripts, learners' weekly reports, and interviews held with the learners after the conclusion of the project. Emotional scaffolding found in the data included expressing positive attitudes toward the chats, complimenting an interlocutor about their FL proficiency, and expressing emotions using emoticons. These types of scaffolding triggered positive emotions in the learners and developed emotional intersubjectivity between the interlocutors, while a lack of emotional scaffolding in the communications led the learners to experience negative emotions. The Challenge: Does emotional scaffolding occur in text chats in a foreign language between learners of the language and native speakers? What kinds of emotions are triggered by emotional scaffolding or lack of emotional scaffolding? How can teachers support learners to develop emotional intersubjectivity in text chats?